2007
DOI: 10.7861/clinmedicine.7-6-585
|View full text |Cite
|
Sign up to set email alerts
|

A discussion of the British Society of Gastroenterology survey of emergency gastroenterology workload

Abstract: -An electronic survey of 188 acute NHS hospitals was carried out to assess the provision of out-of-hours services for gastrointestinal emergencies in England. The response rate was 167/188 (89%) for the main questionnaire and 157/188 (84%) for a supplementary questionnaire. The survey revealed that the majority of gastroenterologists (135/157, 86%) participate in acute general medicine. A rota for out-of-hours endoscopy was in place in only 82/167 (49%) of hospitals. Trained nurse endoscopy assistance was avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…There have been two earlier surveys of the provision of OOH endoscopy services in the UK and it is disappointing that the proportion of hospitals providing a formal OOH service (ie, an on call rota of endoscopists) has not increased from the 50% reported by 150 hospitals in 2002 and the 49% reported in 2005 17 18…”
Section: Discussionmentioning
confidence: 99%
“…There have been two earlier surveys of the provision of OOH endoscopy services in the UK and it is disappointing that the proportion of hospitals providing a formal OOH service (ie, an on call rota of endoscopists) has not increased from the 50% reported by 150 hospitals in 2002 and the 49% reported in 2005 17 18…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] The majority of units in our survey offer an acute gastrointestinal bleed service, although a recent report has raised concerns about the organisation of these services with as many as 64% reporting that arrangements were 'unsatisfactory' . 12 Most hospitals use a combination of sclerotherapy and band ligation for varices, and administer terlipressin. The use of antibiotic prophylaxis has been shown to reduce mortality in variceal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…This difference was not dramatic, as even in hospitals without a formal rota, OOH endoscopies were still being performed on an ‘ad-hoc’ basis, relying on consultant goodwill. Across the UK, there has not been a significant increase in the number of hospitals offering a formal rota, and earlier studies have demonstrated that in 2002 and 2005, 50% and 49% of hospitals, respectively, offered such a service,7 11 which remains deficient in 48% of hospitals 3…”
Section: Discussionmentioning
confidence: 99%